Inhalation of stable dust extract prevents allergen induced airway inflammation and hyperresponsiveness. Issue 2 (21st October 2005) - Peters, M; Kauth, M; Schwarze, J; Körner-Rettberg, C; Riedler, J; Nowak, D; Braun-Fahrländer, C; von Mutius, E; Bufe, A; Holst, O
Abstract : Background: Recent epidemiological studies have shown that growing up on a traditional farm provides protection from the development of allergic disorders such as hay fever and allergic asthma. We present experimental evidence that substances providing protection from the development of allergic diseases can be extracted from dust collected in stables of animal farms. Methods: Stable dust was collected from 30 randomly selected farms located in rural regions of the Alps (Austria, Germany and Switzerland). The dust was homogenised with glass beads and extracted with physiological sodium chloride solution. This extract was used to modulate immune response in a well established mouse model of allergic asthma. Results: Treatment of mice by inhalation of stable dust extract during sensitisation to ovalbumin inhibited the development of airway hyperresponsiveness and airway eosinophilia upon challenge, as well as the production of interleukin 5 by splenocytes and of antigen specific IgG1 and IgE. Dust extract also suppressed the generation of human dendritic cells in vitro. The biological activity of the dust extract was not exclusively mediated by lipopolysaccharide. Conclusions: Stable dust from animal farms contains strong immune modulating substances. These substances can interfere with the development of both cellular and humoral immunity against allergens, thus suppressing allergen sensitisation, airway inflammation, and airway hyperresponsiveness in a murine model of allergic asthma.